Reporting on the causality between oil and gas consumption and economic growth in Nigeria. (1st January 2013) - Omotor, Douglason G.
The slow pace at which the Nigerian economy grew especially in the late 1980s despite the nation's abundant natural resources and large earnings from crude oil and gas production form one of the bases for this study. The objective is to inquire whether there is a causal relationship between data reported on energy consumption (using crude oil and gas) and economic growth. The empirical results which revealed that the variables are stable at various levels prompted the test for cointegration in order to determine whether combinations of the variables are integrated at levels. The individual combinations of the energy consumption variables are not cointegrated with real gross domestic product (GDP). The Granger causality tests also relayed no causal relations between the energy consumption using crude oil and gas and real GDP, thus affirming the 'neutral hypothesis'. The implication of this is that energy conservative policies could be pursued in Nigeria since they may not have adverse effects on the economy